Effect of interfacial crystalline growth on autohesion of PEEK. (March 2019) - Martineau, L.; Chabert, F.; Boniface, B.; Bernhart, G.
Abstract: This work aims to clarify the role of the crystalline growth on the autohesion strength of amorphous PEEK below its melting temperature. The self-bonding strength versus temperature, pressure and time has been measured by lap shear test on 250-micron thick amorphous PEEK assembled at various conditions. The effect of the crystalline growth on the adhesion strength has been established at 155 °C, 200 °C and 250 °C. Autohesion is temperature dependent, whereas pressure at less than 1 MPa and time up to 3 h, have less impact on the adhesion strength. Nevertheless, the evolution of the crystalline morphology with time results in increasing the interfacial strength: a gain of 40% is noticed between 1 and 3 h at 250 °C to reach 0.9 MPa. The degree of crystallinity is higher at the interface than elsewhere in the material, the interface acting as nucleating agent. The evolution of the crystalline morphology at the interface with time shows the refinement of the primary lattice when the temperature is higher than or equal to the previous crystallization temperature, corresponding to the highest temperature seen by the polymeric material. The crystalline growth has an ambivalent effect on the autohesion of PEEK: it reduces the mobility of the macromolecular chains and thus their interdiffusion through the interface and at the same time, it is observed that the improvement of its crystal lattice reinforces the interfacial strength.